Biogeography and Ecological Diversification of a Mayfly Clade in New Guinea - Cozzarolo, Camille-Sophie; Balke, Michael; Buerki, Sven; Arrigo, Nils; Pitteloud, Camille; Gueuning, Morgan; Salamin, Nicolas; Sartori, Michel; Alvarez, Nadir (Frontiers in Ecology and Evolution, 2019)
Understanding processes that have driven the extraordinary high level of biodiversity in the tropics is a long-standing question in biology. Here we try to assess whether the large lineage richness found in a New Guinean clade of mayflies (Ephemeroptera), namely the Thraulus group (Leptophlebiidae) could be associated with the recent orogenic processes, by applying a combination of phylogenetic, biogeographic and ecological shift analyses. New Guinean representatives of the Thraulus group appear monophyletic, with the possible exception of a weakly-supported early-diverging clade from the Sunda Islands. Dating analyses suggest an Eocene origin of the Thraulus group, predating by several million years current knowledge on the origin of other New Guinean aquatic organisms. Biogeographic inferences indicate that 27 of the 28 inferred dispersals (96.4%) occurred during the Eocene, Oligocene and Miocene, while only one dispersal (3.6%) took place during the Pliocene-Pleistocene. This result contrasts with the higher number of altitudinal shifts (15 of 22; 68.2%) inferred during the Pliocene-Pleistocene time slice. Our study illustrates the role played by – potentially ecological - diversification along the elevation gradient in a time period concomitant with the establishment of high-altitude ecological niches, i.e., during orogenesis of the central New Guinean mountain range. This process might have taken over the previous main mode of diversification at work, characterized by dispersal and vicariance, by driving lineage divergence of New Guinean Leptophlebiidae across a wide array of habitats along the elevation gradient. Additional studies on organisms spanning the same elevation range as Thraulus mayflies in the tropics are needed to evaluate the potential role of the ecological opportunity or taxon cycles hypotheses in partly explaining the latitudinal diversity gradient.